ANALISIS UJI KUAT TEKAN PAVING BLOCK DENGAN COMPRESSION TEST DAN HAMMER TEST (Menara: Jurnal Teknik Sipil, 2023)
Based on its quality, paving blocks are used in the construction sector and an alternative choice for surface pavement layers. Several other advantages are concrete bricks (paving blocks) better than other pavements and are economical in maintenance, artistic in terms of the exterior of a building, do not require heavy equipment to work/install, and can be mass-produced. This study aims to compare the compressive strength of paving blocks using a compression test and hammer test and to determine the quality of paving blocks. In this study there are 9 objects, 3 different shapes of paving blocks consist of 3 pieces of each form. The form of paving blocks used are brick paving blocks, hexagons and worms (univape). Based on the test results, there is a difference in the compressive strength value of the compression test and the hammer test, where the compression test compressive strength value is greater than the hammer test compressive strength value. The results of the compressive strength test showed that the paving blocks were in the category of quality B paving blocks.